The Age of Taurus: Environmental Effects on Disc Lifetimes. Issue Volume 10:Issue S314(2015) (November 2015) - Rees, J. M.; Wilson, T.; Bell, C. P. M.; Jeffries, R. D.; Naylor, T.
Abstract: Using semi-empirical isochrones, we find the age of the Taurus star-forming region to be 3-4 Myr. Comparing the disc fraction in Taurus to young massive clusters suggests discs survive longer in this low density environment. We also present a method of photometrically de-reddening young stars using iZJH data.